High Levels of Tumor Necrosis Factor-Alpha Reduce Placental Aquaporin 3 Expression and Impair in vitro Trophoblastic Cell Migration - dos Passos Junior, Rinaldo Rodrigues; de Freitas, Raiany Alves; Reppetti, Julieta; Medina, Yollyseth; Dela Justina, Vanessa; Bach, Camila Werle; Bomfim, Gisele Facholi; Lima, Victor Vitorino; Damiano, Alicia E.; Giachini, Fernanda R. (Frontiers in Physiology, 2021)
Placentas from preeclamptic women display augmented tumor necrosis factor-alpha (TNF-α) levels with reduced expression of aquaporin 3 (AQP3). However, whether TNF-α modulates AQP3 expression remains to be elucidated. We hypothesize that elevated levels of TNF-α reduce AQP3 expression and negatively impact trophoblastic cell migration. Spontaneously hypertensive rats (SHRs) and Wistar rats (14–16 weeks) were divided into hypertensive and normotensive groups, respectively. Systolic blood pressure (SBP) was measured, and animals mated. In a third group, pregnant SHRs were treated with a TNF-α antagonist, etanercept (0.8 mg/kg, subcutaneously) on days 0, 6, 12, and 18 of pregnancy. Placentas were collected on the 20th day of pregnancy. Human placental explants, from normotensive pregnancies, were incubated with TNF-α (5, 10, and 20 ng/ml) and/or etanercept (1 μg/ml). Swan 71 cells were incubated with TNF-α (10 ng/ml) and/or etanercept (1 μg/ml) and subjected to the wound healing assay. AQP3 expression was assessed by Western blot and TNF-α levels by ELISA. SBP (mmHg) was elevated in the hypertensive group, and etanercept treatment reduced this parameter. Placental TNF-α levels (pg/ml) were higher in the hypertensive group. AQP3 expression was reduced in the hypertensive group, and etanercept treatment reversed this parameter. Explants submitted to TNF-α exposition displayed reduced expression of AQP3, and etanercept incubation reversed it. Trophoblastic cells incubated with TNF-α showed decreased cell migration and reduced AQP3 expression, and etanercept incubation ameliorated it. Altogether, these data demonstrate that high TNF-α levels negatively modulate AQP3 in placental tissue, impairing cell migration, and its relationship in a pregnancy affected by hypertension.